2016
DOI: 10.14202/vetworld.2016.1121-1124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tamarindus indica leaf powder on plasma concentrations of copper, zinc, and iron in fluorotic cows

Abstract: Aim:The main objective of the study was to determine the deleterious effect of fluoride on plasma trace minerals of fluorotic cattle and to evaluate the effect of Tamarindus indica leaf powder toward correction of the same.Materials and Methods:A total of 30 cattle exhibiting chronic sign of fluorosis and 10 healthy cattle from nonfluorotic area were incorporated in this study. Fluorotic cattle were divided into three equal groups consisting of 10 cattle each. Group I from fluoride free area served as healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Hence, they can readily bind to biological molecules such as cations, proteins, and enzymes to form stable and strong bonds [105]. For instance, as fluoride is highly electronegative with a strong affinity towards electropositive elements, it binds with calcium, reducing their absorption and causing dental fluorosis and skeletal fluorosis [7]. Moreover, fluoride has been reported to bind to other divalent cations and inhibit many enzymes involved in the pentose phosphate pathway, antioxidant defense system, and myosin-ATPase activity [8,106].…”
Section: Mechanisms Of Environmental Pollutants Toxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, they can readily bind to biological molecules such as cations, proteins, and enzymes to form stable and strong bonds [105]. For instance, as fluoride is highly electronegative with a strong affinity towards electropositive elements, it binds with calcium, reducing their absorption and causing dental fluorosis and skeletal fluorosis [7]. Moreover, fluoride has been reported to bind to other divalent cations and inhibit many enzymes involved in the pentose phosphate pathway, antioxidant defense system, and myosin-ATPase activity [8,106].…”
Section: Mechanisms Of Environmental Pollutants Toxicitymentioning
confidence: 99%
“…Additionally, its beneficial ameliorative effects against fluorosis in laboratory animals was reported [112,113]. Recent studies have tested its effects in fluorotic cattle [7,119]. Gupta et al [119] reported that the supplementation of fluorotic cattle with 100 g of dried powder of Tamarindus indica fruit pulp for 90 days, resulted in a significant increase in serum calcium and alkaline phosphatase levels, and a decrease in urinary hydroxyproline compared to fluorotic cattle not supplemented [119].…”
Section: Fluoride Toxicity Preventionmentioning
confidence: 99%
See 3 more Smart Citations